(untitled) (Italian Journal of Public Health, 2006)
The main purpose of this paper is to explore whether there are differences between men and women in bod- ily consciousness, bodily dissatisfaction and state of affect and if these differences contribute to gender dif- ferences in the reporting of symptoms. A questionnaire was sent out to a randomly selected sample of 1500 persons, between the ages of 25-55 years in Sweden. The results showed that women in this sample were more dissatisfied with their bodies, had higher body awareness and scored higher on the measure of nega- tive affect than men. When considering body consciousness and body esteem in combination with negative affect, the difference between men and women in symptom reporting was reduced, although a considerable gender difference in symptom reporting remained unexplained.